Pengaruh Pembiayaan Berbasis Bagi Hasil terhadap Stabilitas Keuangan Bank Syariah dalam Perspektif Maqashid Syariah - Rika Lisnawati; Muhammad Shaf Karim (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze the effect of profit-and-loss sharing (PLS)-based financing on the financial stability of Islamic banks from the perspective of Maqashid Shariah. The study employs a quantitative explanatory approach using the Structural Equation Modeling - Partial Least Squares (SEM-PLS) method through the WarpPLS 7.0 software. The data used are secondary data obtained from the financial statements of five Islamic commercial banks in Indonesia namely Bank Syariah Indonesia, Bank Muamalat Indonesia, Bank Mega Syariah, Bank Panin Dubai Syariah, and Bank BCA Syariah overing the period 2019 - 2024. The results reveal that PLS-based financing has a positive but statistically insignificant effect on the financial stability of Islamic banks, with a path coefficient of β = 0.28 and a significance value of p = 0.06. Meanwhile, the Maqashid Shariah variable shows a weak positive influence on financial stability (β = 0.10; p = 0.30) and does not significantly moderate the relationship between PLS-based financing and financial stability. The R² value of 0.11 indicates that the model explains only 11% of the variation in financial stability, while the remaining 89% is influenced by other factors such as operational efficiency, macroprudential policies, and capital structure. These findings highlight the need to enhance the systematic implementation of Maqashid Shariah principles in financing policies, risk management, and the development of maqashid-based performance indicators, so that the profit-and-loss sharing principle can function optimally in strengthening the financial stability of Islamic banking in Indonesia.